2011
DOI: 10.5380/ce.v16i1.21118
|View full text |Cite
|
Sign up to set email alerts
|

O Processo De Viver E De Ser Cuidado De Idosos E a Percepção Dos Cuidadores

Abstract: RESUMO:Estudo exploratório descritivo com abordagem qualitativa objetivou conhecer como o idoso percebe o cuidado em saúde e a significação deste em sua vida, e identificar a percepção dos cuidadores leigos e trabalhadores de saúde acerca do cuidado oferecido. Para a coleta de dados utilizou-se entrevista e questionário. A amostra foi constituída de dez idosos institucionalizados e sete domiciliados; seis cuidadores e quatorze trabalhadores. Os dados, analisados pelo referencial da análise de conteúdo, resulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
3
0
4
Order By: Relevance
“…Pode ocorrer a exacerbação ou eclosão de conflitos, provocando estresse e trabalho redobrado ao cuidador. O cuidador precisa identificar as reais necessidades de saúde dos idosos, garantindo sua autonomia, protagonismo e valorização de sua subjetividade 28 . Essa compreensão do cuidador como sujeito que também necessita e demanda por cuidados deve nortear profissionais de saúde nas ações dirigidas a eles.…”
Section: Discussionunclassified
“…Pode ocorrer a exacerbação ou eclosão de conflitos, provocando estresse e trabalho redobrado ao cuidador. O cuidador precisa identificar as reais necessidades de saúde dos idosos, garantindo sua autonomia, protagonismo e valorização de sua subjetividade 28 . Essa compreensão do cuidador como sujeito que também necessita e demanda por cuidados deve nortear profissionais de saúde nas ações dirigidas a eles.…”
Section: Discussionunclassified
“…Those elderly usually receive a pension lower than the wage they earned previously, causing financial losses to the caregiver and significantly overloading this person. Brazilian studies have identified the lack of financial resources as one of the main difficulties in caring for dependent relatives (19)(20) . This situation affects the achievement of the necessary resources to maintain the impaired elderly, favoring the feelings of distress among caregivers, who pursue the best for their dependent relative.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to gender, the results show substantial proportion of women playing the role of family caregivers (96,2%), confirming the results of other studies. 8,12,14,15 Nevertheless, we stress that the assignment of roles and tasks of caring follow cultural norms expecting woman the organization of family life, the care of children and the elderly and all that is related to home. 7 Thus, despite women's emancipation and their growing presence in the labor market, women still tend to take care of the home environment and the health of its members, from children to the elderly and dependents.…”
Section: Resultsmentioning
confidence: 96%